Genetic Analysis of Cadmium Accumulation in Shoots of Sorghum Landraces. Issue 1 (10th November 2016) - Tsuboi, Kana; Shehzad, Tariq; Yoneda, Junichi; Uraguchi, Shimpei; Ito, Yusuke; Shinsei, Lin; Morita, Shoji; Rai, Hiroki; Nagasawa, Nobuhiro; Asari, Keiko; Suzuki, Hiroko; Itoh, Rumiko; et al.
Abstract : Contamination of agricultural fields with heavy metals, such as Cd, is a serious issue for safe food production worldwide. Previous reports indicate that sorghum [ Sorghum bicolor (L.) Moench] is useful for phytoextraction of Cd from contaminated soils. To investigate the diversity for Cd accumulation in sorghum germplasm and to select useful cultivars for phytoextraction, we conducted experiments using 106 sorghum landraces and the cultivar BTx623, grown in hydroponic cultures and under field conditions. The Cd concentrations in plant shoots of different landraces showed no correlation between hydroponic and field‐grown plants ( r = −0.16). We measured Cd concentrations in various plant parts at different stages of development in field‐grown plants and found that leaf sheaths often had higher Cd concentrations than other plant parts. Our results indicated that screening could be done for plants that might be useful for phytoextraction of Cd by determining the Cd concentrations in leaf sheaths of 1‐mo‐old plants grown in a Cd‐contaminated soil. We also mapped the quantitative trait loci (QTLs) responsible for Cd accumulation in sorghum shoots and found several chromosomal regions that affected Cd concentrations in different parts of the shoot. We were able to identify several promising landraces for developing sorghum cultivars that are capable of accumulating high levels of Cd and phytoextracting Cd from contaminated soils.